Song type and song type matching are important for joint territorial defense in a duetting songbird. (17th June 2021) - Wheeldon, Amie; Szymański, Paweł; Surmacki, Adrian; Osiejuk, Tomasz S
Abstract: Birds have a diverse acoustic communication system, with species-specific repertoires facilitating more complex behaviors in terms of both within- and between-pair communications. Certain song types are produced for specific functions, such as aggressive encounters. In addition, song matching behaviors, whereby neighboring individuals match song types, can be used in aggressive interactions as a sophisticated acoustic behavior. In this study, we examined the functions of song types, in a duet context, of male yellow-breasted boubous ( Laniarius atroflavus ), an Afromontane bush-shrike with a vocal sexual dimorphism. We aimed at assessing whether, structurally, certain song types elicited a heightened reaction than others and also whether song matching affected response behavior. A dual speaker playback procedure was performed for 18 pairs of boubous, each pair being exposed to duets with three different male song types. We found differences in response toward the different duet types but these differences resulted from the amount at which males matched different song types. Pairs responded stronger when a focal male matched the playback type, and matching was significantly more often found in cases where the rarest type of male song was used. We found no sex differences in terms of response strength to playback type. Our results indicate a two-level way of coding aggression toward intruding pairs. The yellow-breasted boubous utilize their repertoires, linking matching with structure in order to show aggression in terms of territory defense and sexual conflict. This study also confirms joint territorial defense as a main function of duets in this species. Abstract : The diverse song repertoires of birds, in terms of size and organization, facilitate both within- and between-pair communication. Using playback experiments, we showed that males and females of a duetting Afromontane bush-shrike jointly defend territories. The small and shared repertoire of male songs is important for conflict resolution. Our results indicate a two-level way of coding aggression toward territory intruders. Both, song type used and matching a male intruders song type, shape the response strength.